Discovery and preclinical characterization of the antagonist anti-PD-L1 monoclonal antibody LY3300054. Issue 1 (30th April 2018) - Li, Yiwen; Carpenito, Carmine; Wang, George; Surguladze, David; Forest, Amelie; Malabunga, Maria; Murphy, Mary; Zhang, Yiwei; Sonyi, Andreas; Chin, Darin; Burtrum, Douglas; Inigo, Ivan; et al.
Abstract : Background: Modulation of the PD-1/PD-L1 axis through antagonist antibodies that block either receptor or ligand has been shown to reinvigorate the function of tumor-specific T cells and unleash potent anti-tumor immunity, leading to durable objective responses in a subset of patients across multiple tumor types. Results: Here we describe the discovery and preclinical characterization of LY3300054, a fully human IgG1λ monoclonal antibody that binds to human PD-L1 with high affinity and inhibits interactions of PD-L1 with its two cognate receptors PD-1 and CD80. The functional activity of LY3300054 on primary human T cells is evaluated using a series of in vitro T cell functional assays and in vivo models using human-immune reconstituted mice. LY3300054 is shown to induce primary T cell activation in vitro, increase T cell activation in combination with anti-CTLA4 antibody, and to potently enhance anti-tumor alloreactivity in several xenograft mouse tumor models with reconstituted human immune cells. High-content molecular analysis of tumor and peripheral tissues from animals treated with LY3300054 reveals distinct adaptive immune activation signatures, and also previously not described modulation of innate immune pathways. Conclusions: LY3300054 is currently being evaluated in phase I clinical trials for oncology indications.